2001
DOI: 10.1046/j.1432-1327.2001.01831.x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of insulin receptor substrates in epidermal growth factor induced activation of phosphatidylinositol 3‐kinase in rat hepatocyte primary culture

Abstract: Short-term incubation of adult rat hepatocytes with epidermal growth factor (EGF) caused tyrosine phosphorylation of insulin receptor substrate (IRS)-1 and IRS-2 when the cells had been submitted to primary culture from 1±18 h. Tyrosine-phosphorylated IRS-1 and IRS-2 bound to the regulatory subunit (p85) of phosphatidylinositol (PtdIns) 3-kinase, thereby activating the enzymic activity. Tyrosine phosphorylation of the IRSs and activation of PtdIns 3-kinase in 3 h cultured hepatocytes both proceeded similarly t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 52 publications
4
17
1
Order By: Relevance
“…The finding that EGF elicits the phosphorylation of both IRS-1 and IRS-2 is in agreement with the recent work of Fujioka et al in cultured rat hepatocytes as well as A431 cells abundantly expressing EGFR (38,44). These authors reported that EGFR directly phosphorylated IRS-1 in in vitro assays (44) and that this was markedly attenuated if the C-terminal of EGFR was truncated.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The finding that EGF elicits the phosphorylation of both IRS-1 and IRS-2 is in agreement with the recent work of Fujioka et al in cultured rat hepatocytes as well as A431 cells abundantly expressing EGFR (38,44). These authors reported that EGFR directly phosphorylated IRS-1 in in vitro assays (44) and that this was markedly attenuated if the C-terminal of EGFR was truncated.…”
Section: Discussionsupporting
confidence: 92%
“…The EGF receptor has three potential PTB-binding sites allowing for an interaction with substrates like IRS-1 (38) and IRS-2. The present data clearly show that EGF increases the tyrosine phosphorylation of the same signaling molecules as seen with insulin and, in addition, Gab1 as well as its cognate receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Steroids are involved in conversion of cholesterol to VLDL and exertion of cholesterol as the bile. Thus, the increased VLDL as long as decreased total serum level of cholesterol in T. terrestris treated rats could be explained by steroids component of the extract (Fujioka & Ui, 2001). Saponin is another component of the extract not only regulates lipid metabolism but also improves hypercholesterolemia and hypertriglyceridemia (Yan et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this component of the extract could reduce the absorption of fructose and also interrupt the fructose metabolization to lipids (Gosain et al, 2010). Steroids are involved in conversion of cholesterol to VLDL and exertion of cholesterol as the bile.…”
Section: Discussionmentioning
confidence: 99%
“…EGF-induced IRS1 modification was not unique to HT-29 cells: EGFR-dependent IRS1-Tyr 896 phosphorylation was also observed in A431 epidermoid carcinoma cells. 4 EGF has previously been reported to promote tyrosine phosphorylation of IRS1, but specific sites of phosphorylation have not been identified (43)(44)(45). To search for candidate IRS1-Tyr 896 kinases, we used the Scansite motif-based searching algorithm (46), which compares Swiss-Prot protein sequences to experimentally determined consensus sites for dozens of protein kinases.…”
Section: Key Features Of the Signaling Compendium Identified By Cytokmentioning
confidence: 99%